Chagas Cardiomyopathy Presenting as Symptomatic Bradycardia: An Underappreciated Emerging Public Health Problem in the United States - Richard Jesse Durrance; Tofura Ullah; Zulekha Atif; William Frumkin; Kaushik Doshi (Case Reports in Cardiology)
Chagas cardiomyopathy (CCM) is traditionally considered a disease restricted to areas of endemicity. However, an estimated 300,000 people living in the United States today have CCM, of which its majority is undiagnosed. We present a case of CCM acquired in an endemic area and detected in its early stage. A 42-year-old El Salvadoran woman presented with recurrent chest pain and syncopal episodes. Significant family history includes a sister in El Salvador who also began suffering similar episodes. Physical exam and ancillary studies were only remarkable for sinus bradycardia. The patient was diagnosed with symptomatic sinus bradycardia and a pacemaker was placed. During her hospital course, Chagas serology was ordered given the epidemiological context from which she came. With no other identifiable cause, CCM was the suspected etiology. This case highlights the underrecognized presence of Chagas in the United States and the economic and public health importance of its consideration in the etiological differential diagnosis of electrocardiographic changes among Latin American immigrants. While the United States is not considered an endemic area for Chagas disease, the influx of Latin American immigrants has created a new challenge to identify at-risk populations, diagnose suspected cases, and provide adequate treatment for this disease.